PENGUJIAN EKSPERIMENTAL DAN SIMULASI ANSYS PERFORMANSI POMPA SENTRIFUGAL RANGKAIAN SERI DAN PARALEL - Pohan, Adam Hafizar (Jurnal Sistem Teknik Industri, 2018)
This study was conducted to identify the performance of centrifugal pump series configuration and parallel configuration experimentally and Ansys simulation. In the previous study, the performance of centrifugal pumps was calculated by varying the valve opening. In this study researchers varied motor rotation of 1000 rpm, 1200 rpm, 1400 rpm, 1600 rpm and 1800 rpm with open valve 100%. The results show that series configuration has higher head value than parallel configuration. While the parallel configuration has a higher capacity value than the series configuration. The highest pump efficiency for this pump performance test is in series configuration of 1800 rpm is 83.4% for experimental and 85% for simulation. While the lowest pump efficiency is in parallel configuration pumps of 1800 rpm with an efficiency 14.1% for experimental and 15.5% for simulation.